Enhancing CO2/CH4 Separation Using Ppo-derived Hollow Fiber Carbon Membrane - Jaya M. A. T.; Jalani M.A.; Yusop M. F. M.; Gonawan F. N.; Nizam M.K.; Ismail A. F.; Ahmad M. A. (Asian Scholars Network, 2024)
Non-Indexed Publication